2007
DOI: 10.1002/qua.21416
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemical simulation of cytochrome P450 catalyzed aromatic oxidation: Metabolism, toxicity, and biodegradation of benzene derivatives

Abstract: ABSTRACT:The dependences of biological oxidation and toxicity of the mono-and multisubstituted benzene derivatives on the nature of substituents are studied using an oxenoid model and the quantum chemical calculations. According to this model, the P450 enzyme breaks the dioxygen molecules and generates the active atomic oxygen species (oxens); these species readily react with substrates. Using MO LCAO MNDO approach, we calculated the differences ⌬E of the total energies of aromatic compounds and corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…In summary, taking into account our previous results 18, we conclude that the oxenoid model together with semiempirical quantum chemical calculations can reasonably explain the in vivo and in vitro experimental data on the positions of the enzyme‐mediated oxidation, rate of substrate biotransformation, as well as toxicity, and carcinogenicity of the mono‐ and disubstituted benzene derivatives.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In summary, taking into account our previous results 18, we conclude that the oxenoid model together with semiempirical quantum chemical calculations can reasonably explain the in vivo and in vitro experimental data on the positions of the enzyme‐mediated oxidation, rate of substrate biotransformation, as well as toxicity, and carcinogenicity of the mono‐ and disubstituted benzene derivatives.…”
Section: Discussionsupporting
confidence: 68%
“…The oxens readily react with substrates 16, 17. The relationships between the nature of substituents from one side and biological oxidation and acute toxicity of the benzene derivatives from another side as well as the features of metabolism of di‐ and trichlorinated biphenyls by bacteria were studied using an oxenoid model in our recent paper 18.…”
Section: Introductionmentioning
confidence: 99%
“…The results at the AM1 level are rather poor ( r 2 = 0.55 for BDE cat alone, excluding nonaromatic oxidations, and r 2 = 0.60 for our full data set with both descriptors). However, it is significantly better and faster than energies obtained for the intermediate with the methoxy-radical model ( r 2 = 0.35−0.45), a method that has been used in several previous studies. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…It has previously been shown that the methoxy radical can be used as a model for compound I when studying the hydroxylation of aliphatic carbon atoms , as well as in semiempirical studies of hydroxylation of aromatic carbon atoms. ,,, Therefore, we also tested how well the activation energies and the energies of the tetrahedral intermediate, calculated with the methoxy radical could reproduce the energies in Table . As is shown in part a of Figure and Table , the activation energies calculated with the methoxy radical at the B3LYP/6−31G(d) level correlate well with the final DFT energies calculated with the full compound I model.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative relationships between structure and metabolism rates have been investigated for a limited number of closely related compounds, even though their applicability to PBPK modeling has not been demonstrated (e.g., QSPR models for K cat and 1/ K m [ 87 ]). Other works in this area relate to the development of quantum chemical or quantum dynamic methods for prediction of activation energy or enthalpy of activation of P450 mediated reactions [ 20 , 25 , 26 , 31 , 36 , 38 , 88 91 ], which have not been used to derive metabolism constants for direct incorporation within rodent or human PBPK models.…”
Section: Discussionmentioning
confidence: 99%